International Intervention and Genocide in Bosnia - Gamawa, Yusuf Ibrahim (Advances in Social Sciences Research Journal, 2017)
The United Nations intervention in the Bosnian conflict was generally considered a positive development that could bring an end to the instabilty in the Balkans after the dissolution of Yugoslavia. The UN was forced to intervene following the outbreak of violence in Bosnia after the referendum for its independence, a move that came to strongly resisted resisted by the Serbs. The UN togather with NATO collaborated on the Bosnian operations with aim of protecting the population as well as bringing stability. Arms embargo was imposed the UN, and safe areas were created, and among them them was Srebrenica. The UN declared such areas safe and free from attack when in reality it did not put in place in effective force in these areas to repel or counter attacks from any group. The result was the massacre of about 8,000 Bosnian before the UN peace keeping force by the Bosnian Serbs. The intervention in Bosnia as result raised many questions regarding UN policies and role, to the extent that it is argued if the intervention was actually carried out in accordance with the established humanitarian intervention ethics and the responsibility to protect. Why did the UN declare certain areas safe when it fully aware that it lacked the ability to protect the population of the areas from attacks? Rather than protect, The UN intervene in Bosnia appeared to have created an opportunity for mass murder or what came to be known as the Bosnian genocide. This paper argues that the intervention in Bosnia fell short of complying with the principles and ethic of humanitarian interventions as will be shown in the article.